Simultaneous production of high-valued carbon nanotubes and hydrogen from catalytic pyrolysis of waste plastics The role of cellulose impurity - Liu, Qingyu (Waste management (New York, N.Y.), 2024)
Copyright © 2023 Elsevier Ltd. All rights reserved.